Evaluasi Pembelajaran Sekolah Dasar Berbasis Pendidikan Karakter dan Multikultural - Marliyah, Marliyah (PGMI IAIN Lhokseumawe, 2024)
Learning evaluation is the overarching concept which both depends upon measurements and assessment to make a composite judgment or decision. Character education and multicultural learning evaluation in elementary school (SD) adjusted with level thinking of the children in elementary school. Where there are still in early stages of the abstract. Character education is a system of cultivation of character values to the school community, which includes knowledge, awareness or volition, and actions to implement these values, both of the Almighty God (Almighty), ourselves, others, the environment, and national so that the perfect man to be human. While, indeed multicultural education becomes an integral part in all levels of education. Therefore the value investment multicultural ideally applied in all of subjects at formal education.